Dynamics of Civil Structures, Volume 4 Proceedings of the 32nd IMAC, A Conference and Exposition on Structural Dynamics, 2014 - Catbas, Fikret Necati.; Catbas, Fikret Necati. (Conference Proceedings of the Society for Experimental Mechanics Series,, 2014)
This critical collection examines a range of the dynamics of civil structures, from dynamic testing of civil structures to bridge structures to operational modal analysis, as presented in early findings and case studies from the Proceedings of the 32nd IMAC, A Conference and Exposition on Structural Dynamics, 2014. The collection includes papers in the following general technical research areas:   ·         Modal Parameter Identification ·         Dynamic Testing of Civil Structures ·         Human Induced Vibrations of Civil Structures ·         Correlation & Updating ·         Operational Modal Analysis ·         Damage Detection of Structures ·         Bridge Structures ·         Damage Detection Models ·         Experimental Techniques for Civil Structures.